Secrecy Performance Analysis of Energy Harvesting Untrusted Relay Networks with Hardware Impairments - Dechuan Chen; Jin Li; Jianwei Hu; Xingang Zhang; Shuai Zhang; Dong Wang (International Journal of Distributed Sensor Networks)
In this work, we focus on the issue of secure communication in energy harvesting untrusted relay networks taking into account the impact of hardware impairments, where an energy-constrained relay, powered by received radio frequency signals, attempts to decode sensitive data from the source without authorization. To achieve secure communication, we employ destination-assisted jamming to prevent the untrusted relay from decoding sensitive data while serving as a useful energy source. We derive the interception probability (IP), connection outage probability (COP), and effective secrecy throughput (EST) in closed form for time switching relaying (TSR) strategy. Subsequently, we conduct an asymptotic analysis in the high signal-to-noise ratio (SNR) regime to provide practical insights into how various system parameters affect security, reliability, and efficiency, including time switching factor and the level of hardware impairments. Our findings demonstrate that the presence of hardware impairments improves security performance but compromises reliability performance, which does more harm than good.